Behavioral economics and healthy behaviors key concepts and current research - Hanoch, Yaniv; Barnes, Andrew J. (Routledge, Taylor & Francis Group, 2017)
"The book opens with an overview of the core theoretical concepts, after which each chapter assesses how behavioral economic research and practice can inform public policy across a range of health issues. Including chapters on tobacco, alcohol and drug use, physical activity, dietary intake, cancer screening and sexual health, the book integrates the key insights from the field to both developed and developing nations."--Provided by publisher.